The impact of investment in agricultural research and development and agricultural productivity - Perez, Nicostrato D.; Rosegrant, Mark W. (International Food Policy Research Institute, 2015)
This study was conducted to determine the impact on world prices, agricultural commodities production, and food security and nutrition of raising the annual growth in agricultural total factor productivity (TFP) from the current estimate of 1.6 percent to 2 percent by 2030 through investment in agricultural research and development (R&D). The study also compared three R&D investment strategies: (1) gradual TFP increase, (2) accelerated TFP increase, and (3) developing-countries-only TFP increase. Results show that compared with the baseline scenario of business as usual, R&D investment strategies to increase TFP to 2 percent can lower world prices of cereals and meat by as much as 17 and 15 percent, respectively, as well as increase area planted in crops by 2.4 percent and crop yields by 8.5 percent by 2030. World cereal and meat production can also be increased by 12.5 and 3.9 percent, respectively, and consumption by 4.5 and 3.9 percent, respectively. The number of malnourished children can be reduced by 7 million (5.4 percent), and the population at risk of hunger can be reduced by 160 million (23.2 percent).